Influence of Social Support on Breastfeeding Practice - Lina Handayani; Azlina Md Kosnin; Yeo Kee Jiar (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2011)
Social and environmental factors are common influencing factors in the decision of breastfeeding. This paper reports a systematic literature review about the influence of social support on breastfeeding practice around the world. An online literature search was conducted in Science Direct, Cochrane Database of systematic reviews, PubMed, WileyInterScience, and SpringerLink. There are three resources of social support: family, peer, and professional. All of the studies show the similar results; social support influences breastfeeding practice.